Antibacterial and Antifungal Properties of Electrospun Recycled PET Polymeric Fibers Functionalized with Zinc Oxide Nanoparticles - Katherine Vázquez (MDPI AG, 2021)
Currently, to reduce the environmental problems associated with plastic waste, methods are being sought to use this waste as raw materials in different applications, such as fibers. In addition, to improve these materials and provide different properties, nanoparticles (NPs) are incorporated. In the present work, polymeric fibers made of recycled polyethylene terephthalate (r-PET) from post-consumer water bottles, functionalized with 0%, 1.5%, 3% and 6% zinc oxide nanoparticles (ZnO-NPs) in function of r-PET weight, were elaborated to evaluate their antibacterial and antifungal characteristics. The ZnO-NPs were synthesized by the solvothermal method, obtaining particles with a mean diameter of 38.15 nm, while the fibers were obtained by electrospinning with a diameter range between 200–5000 nm. The functionalized fibers were carried out against Escherichia coli and Bacillus subtilis through the agar diffusion method, obtaining the highest inhibition halo at 6% w/w ZnO-NPs, being 26.5 mm and 34.25 mm, respectively. In addition, the same method was used to evaluate the antifungal activity of Penicillium s.p. and Fusarium graminearum, observing antifungal properties due to the presence of nanoparticles in the fibers.